Réponses

  • Utilisateur Brainly
2014-03-13T07:42:14+01:00
Bonjour,

Factoriser : 

A= 36x² - 36x + 9
A= (6x - 3)
²

B= (4x + 9)
² - 36
B= (4x + 9 - 6)(4x + 9 + 6)
B= (4x + 3)(4x + 15)

C= 4x
² + 32x + 64
C= (2x + 8)²

Bonne journée! :)
2014-03-13T08:00:28+01:00
A = 36x² - 36 x + 9

Cette expression est de la forme a
²-2ab+b² avec a = 6x et b = 3 : 
               36x² - 36 x + 9 ⇒ (6x)² - 2*6x*3 + (3)²

Rappel : a²-2ab+b² = (a-b)²

 36x² - 36 x + 9 = (6x-3)²

B = (4x+9)²-36 = (4x+9)²-(6)² . Cette expression est de la forme a²-b² avec a = 4x+9 et 
                                                b = 6

Rappel : a²-b² = (a+b)*(a-b)

 (4x+9)²-36 = (4x+9+6)(4x+9-6)
                  = (4x+15)*(4x+3)

C = 4x
²+32x+64 . 

Cette expression est de la forme a²+2ab+b² avec a = 2x et b = 8 :
                      4x²+32x+64 = (2x)²+2*2x*8+(8)²

Rappel : a²+2ab+b² = (a+b)²

4x²+32x+64 = (2x+8)²